Uji Aktivitas dan Keamanan Kombinasi Ekstrak Bawang Putih (Alium sativum.l) dan Ekstrak Kemiri (Aleurites molucanna) sebagai Penyubur Bulu Kelinci - Misde Yola; Agung Wibowo; Shelly Thaurhesia (Universitas Borneo Lestari, 2021)
Candlenuts and Garlic are plants that have an effect on the growth of hair. Chemical contained in the plant is rich in nutrients needed for hair or eyebrow growth . Efficacy of candlenut oil and garlic oil with three concentrations of 1000 ppm, 500 ppm and 100 ppm tested its activity as fertilizer of rabbit fur by applying hazelnut oil and garlic oil each of approximately 1 ml at spot prepared twice daily for 28 days. The result of the third activity test of this concentration tested the data with statistics and got the most optimum result as grower of rabbit fur is candlenuts oil with the concentration of 1000 ppm with the average growth of length for 28 days is 0,6250 cm and garlic oil with concentration 500 ppm with the average length of growth for 28 days is 0.8417 cm, while for the most optimum rabbit fur weights are with garlic concentration of 1000 ppm with an average weight of 28 days is 0.3627 g, while the growth of rabbit fur weight most optimum for 28 days is candlenut 1000 ppm with average weight for 28 days = 0.3518 g result of significant analysis at (p≤0,05). The most significant efficacy of candlenut oil and garlic oil combined was the combination with the ratio of pecan oil and garlic is 1: 1 with concentration (200: 200) ppm.